A case of polymorphic leukocytoclastic vasculitis associated with renal neoplasia - A. A. Klimenko; N. A. Shostak; A. S. Gaffarova; A. A. Kondrashov; E. I. Schmidt (Klinicist)
Objective: to describe a clinical case of polymorphic leukocytoclastic vasculitis (PLCV) associated with renal neoplasia.Materials and methods. Patient K., a man, 67 y. o., was admitted to the surgical department No. 2 of the N. I. Pirogov State Clinical Hospital No. 1 with cardiac complaints and heart failure decompensation symptoms, severe respiratory insufficiency associated right lower lobe pneumonia. Besides cardiac function evaluation and pneumonia managing there was a conducting of differential diagnostic search to clarify the genesis of ulcerative necrotic rashs among systemic vasculitis, paraneoplastic syndrome including hematologic problems and sepsis.Results. It was no data for systemic connective tissue diseases and systemic vasculitis during clinical examination and immunological diagnostics. On contrast-enhanced multispiral computed tomography of abdomen and retroperitoneal space there was latent malignant neoplasia of left kidney Т2аN1M0. PLCV was considered to paraneoplastic syndrome associated with malignancy. Due to the progression of vasculitis and the patient’s refusal of surgical treatment was prescribed GC 0.5 mg / kg / day as a result positive dynamics was noted.Conclusion. This clinical case demonstrates necessity of providing examination aimed at malignancy excluding for early neoplasm’s detecting for patients with vasculitis.